Characteristics of atmospheric polycyclic aromatic hydrocarbons (PAHs) in gas and particle phase in April and July 2011 in Beijing, China - Cheng, Xiao Liang; Shaodong Xie (Advanced Materials Research, 2013)
Presence of atmospheric PAHs in urban and suburban region (Beijing, China) was studied in April and July 2011. Forty-four pairs of gas and particle (TSP) phase samples were collected every six day by high volume (Hi-Vol) air samplers at four sampling sites, and determined separately by GC/MS based on USEPA Method TO-13A. Average total concentration (gas + particles) of PAHs (T-PAHs) was 135.1±49.0 ng/m3 and 181.2±40.9 ng/m3 in April and July, respectively. Gas phase PAHs (G-PAHs) was the major fraction, comprising 63–92% of T-PAHs. Lighter (2-, 3-, 4-ring) and heavier (5-,6-ring) PAHs were found predominantly in gas and particle phase, respectively. 2- to 6- ring PAHs contributed 10%, 53%, 26%, 7% and 4% of T-PAHs, respectively. Five major PAHs, naphthalene (NAP), fluorene (FLU), PHE, fluoranthene (FLA), and pyrene (PYR) contributed 70 – 90% of T-PAHs. G-PAHs increased significantly while PAHs in particle phase (P-PAHs) decreased from April to July. Volatilization from soil and more emission from power generation increase might explain the increase of G-PAHs, and the washout of P-PAHs along with particles might explain the decrease of P-PAHs. Given particulate organic carbon (OC) and elemental carbon (EC) being well correlated, P-PAHs was moderately correlated with OC and EC, suggesting that there were other mechanisms contributing to P-PAHs different from those of OC/EC. Significant correlation between P-PAHs with SO2 and NO2 suggested coal combustion and automobile exhaust to be contamination contributors.